Disparities in magnetic resonance imaging of the prostate for traditionally underserved patients with prostate cancer. Issue 16 (17th June 2021) - Quinn, Timothy P.; Sanda, Martin G.; Howard, David H.; Patil, Dattatraya; Filson, Christopher P.
Abstract : BACKGROUND: Prebiopsy magnetic resonance imaging (MRI) of the prostate improves detection of significant tumors, while decreasing detection of less‐aggressive tumors. Therefore, its use has been increasing over time. In this study, the use of prebiopsy MRI among Medicare beneficiaries with prostate cancer was examined. It was hypothesized that patients of color and those in isolated areas would be less likely to undergo this approach for cancer detection. METHODS: Using cancer registry data from the Surveillance, Epidemiology, and End Results (SEER) program linked to billing claims for fee‐for‐service Medicare beneficiaries, men with nonmetastatic prostate cancer were identified from 2010 through 2015 with prostate‐specific antigen (PSA) <30 ng/mL. Outcome was prebiopsy MRI of the prostate performed within 6 months before diagnosis (ie, Current Procedural Terminology 72197). Exposures were patient race/ethnicity and rural/urban status. Multivariable regression estimated the odds of prebiopsy prostate MRI. Post hoc analyses examined associations with the registry‐level proportion of non‐Hispanic Black patients and MRI use, as well as disparities in MRI use in registries with data on more frequent use of prostate MRI. RESULTS: There were 50, 719 men identified with prostate cancer (mean age, 72.1 years). Overall, 964 men (1.9% of cohort) had a prebiopsy MRI. Eighty percent of patients with prebiopsy MRI lived in California, New Jersey, or Connecticut. Non‐Hispanic Black men (0.6% vs 2.1% non‐Hispanic White; odds ratio [OR], 0.28; 95% CI, 0.19‐0.40) and men in less urban areas (1.1% vs 2.2% large metro; OR, 0.65; 95% CI, 0.44‐0.97) were less likely to have prebiopsy MRI of the prostate. CONCLUSIONS: Non‐Hispanic Black patients with prostate cancer and those in less urban areas were less likely to have prebiopsy MRI of the prostate during its initial adoption as a tool for improving prostate cancer detection. Abstract : During a phase of its initial adoption, non‐Hispanic Black men and men in rural areas were less likely to have prebiopsy magnetic resonance imaging of the prostate before their cancer diagnosis. This was not related to population characteristics in regions that were more likely to use this method of prostate cancer detection.